Peningkatan Kapasitas Petani dalam Pembuatan Pupuk Organik Cair (POC) Ramah Lingkungan di Desa Rumah Tiga, Kota Ambon Propinsi Maluku - Asrul, Asrul; Liputo, Burhan; Hamka, Hamka (-, 2025)
The training on the production of liquid organic fertilizer (LOF) conducted in Rumah Tiga Village, Teluk Ambon District, Ambon City, aimed to enhance farmers' capacity in implementing environmentally friendly and sustainable agricultural practices. The program engaged six farmer groups and adopted a participatory approach that integrated theoretical instruction with hands-on practice. Farmers were trained to produce LOF using locally available organic materials such as banana stems and household kitchen waste. The training resulted in a significant improvement in participants’ knowledge and skills, with 90% of trainees able to accurately recall the LOF production procedures. Furthermore, 82% of participants expressed a strong commitment to independently adopt LOF in their farming activities. The program also contributed to strengthening social capital by increasing participation in communal activities (gotong royong) and encouraging the formation of informal learning groups. These findings indicate that participatory, practice-based training models are effective in fostering behavioral change among farmers toward sustainable agriculture and can be replicated in other regions as a strategic approach to empowering farming communities.